In Vitro Regeneration of Eucalyptus pellita F. Muell by Mutiple-Node Culture - Toni Herawan; Budi Leksono (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2018)
Plantation of Eucalyptus pellita F. Muell in the Industrial Plantation Forest (HTI) progam have applied a clonal forestry system to improve productivity of mean annual increament and homogenous plants on each rotation. However, the productivity has been low and not meet the need of raw materials for pulp industry. The objectives of the research is to develope of E. pellita in vitro by multiple node culture to increase shoots growth at each step in vitro propagation. Combination of in vitro and macro propagation in establishing hedge orchard (mini cutting) is the best technique and efficient to propagate and optimize of the growth of the species. The method to increase the successful of E. pellita in vitro at the induction step was using mutiple-node culture and application of rotary shaker. Four treatments were applied at multipication, rooting and acclimatization steps to obtain the best combination of media for E. pellita in the optimum condition. The results showed that application of rotary shaker increased the shoots growth at the induction step and accelerated the shoots growth at the multiplication step.The procedure applied in this study was also resulting an optimal and efficient response of shoots and roots growth in each step (induction, multiplication, rooting) of E. pellita in vitro until acclimatization in the greenhouse.